(untitled) (Journal of the College of Basic Education, 2022)
Volleyball is one of the games that occupied a wide space among its fans and followers, just like the rest of the other organized games, because it is characterized by a special character that distinguishes it from the rest of the games due to the nature of the modern performance of the game and as a result of the amendments and changes that occurred in the law of the game. The psychological preparation of the players also plays an important role in achieving the achievement.